Psychological well-being, marital conflict and marital satisfaction of selected Ilonggo women in interracial marriages. - Torrefranca, Shara Mae L.
This study sought to examine the effect of being interracially married to the state of psychological well being, marital conflict and marital satisfaction of Filipino women. Questionaires and interviews were administered in gathering the data. Results showed that Filipino women were motivated by several factor s in entering into interracial marriages. They generally apprehended that destiny and good personality attracted them to marry a foreighner husband. Other common reasons include their proximity to foreigners because of employment outside the country, some already had personal intentions of marrying spouses from other nationalities, foreigners are are to be a good providers and they possessed good physical qualities. They offered an understanding that regardless of their husband's race, they displayed a physical well being. Marital conflicts were indeed present in their marriages in the form of personal and social sources, with the former greater weight. Taken as a whole, respondents reported living a satisfied married life.